2015
DOI: 10.1177/0141076815604494
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions and recall of consent for regional anaesthesia compared with consent for surgery

Abstract: SummaryObjective: In Britain, consent for surgery is documented using a Department of Health form signed by the surgeon and the patient. In contrast, anaesthetic procedures have no formalised consent process. Evidence on the process of consent for regional anaesthesia, and patient perceptions of this, is scarce outside obstetric practice. We aimed to determine patient recall and perceptions of consent for interscalene brachial plexus block and compared this to surgical consent for shoulder arthroplasty. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
0
16
0
7
Order By: Relevance
“…For example, a discussion about testing may not be viewed by patients with the same gravitas as a signed consent form, or patients may fail to recognize it as part of the consent process [62]. Also, the information disclosed in patient-provider discussion may vary substantially due to providers' knowledge [63][64][65][66], so provider education is essential and discussion tips may help standardize discussions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a discussion about testing may not be viewed by patients with the same gravitas as a signed consent form, or patients may fail to recognize it as part of the consent process [62]. Also, the information disclosed in patient-provider discussion may vary substantially due to providers' knowledge [63][64][65][66], so provider education is essential and discussion tips may help standardize discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of surgical indications, procedure details and especially recall of risks have been used in previous studies to assess consent. 10,12,13 We used similar parameters in our study to objectively assess informed consent, as well as patient satisfaction of the consenting process. Every patient had a standard discussion with an appropriate clinician and opportunity to ask questions, receiving the same hospital information leaflet at their initial consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Zarnegar and colleagues previously conducted a small (n=46) survey to compare memory of risks related to ISB compared with those related to surgery, which were disclosed prior to shoulder arthroplasty. 6 These investigators found that patients had poor memory of ISB risks, with almost half of the participants unable to identify a single risk that had been previously disclosed. However, several methodological shortcomings undermine the study's validity, including incomplete and heterogeneous risk disclosure, inconsistent documentation of the consent discussions, lack of consideration for participants' language and educational levels, small sample size, and possible recall bias due to the prolonged delay between risk disclosure and subsequent memory assessment and data collection.…”
Section: Original Articlementioning
confidence: 99%